2009
DOI: 10.2166/wst.2009.609
|View full text |Cite
|
Sign up to set email alerts
|

Two strategies for phosphorus removal from reject water of municipal wastewater treatment plant using alum sludge

Abstract: In view of the well recognized need of reject water treatment in MWWTP (municipal wastewater treatment plant), this paper outlines two strategies for P removal from reject water using alum sludge, which is produced as by-product in drinking water treatment plant when aluminium sulphate is used for flocculating raw waters. One strategy is the use of the alum sludge in liquid form for co-conditioning and dewatering with the anaerobically digested activated sludge in MWWTP. The other strategy involves the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Increasing interest in the usage of WWS for the removal of phosphate at the WWTP is seen in the past two decades in the form of many laboratory studies (e.g. Babatunde and Zhao 2010;Ippolito et al 2003;Yang et al 2009;Zhao et al 2007); however, the reuse of WWS at WWTP is rarely seen in practice. The reported studies on phosphate removals with WWS show that the sorption of phosphate is a two-stage process: a quick sorption followed by slow sorption (cited in Ippolito et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing interest in the usage of WWS for the removal of phosphate at the WWTP is seen in the past two decades in the form of many laboratory studies (e.g. Babatunde and Zhao 2010;Ippolito et al 2003;Yang et al 2009;Zhao et al 2007); however, the reuse of WWS at WWTP is rarely seen in practice. The reported studies on phosphate removals with WWS show that the sorption of phosphate is a two-stage process: a quick sorption followed by slow sorption (cited in Ippolito et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence the majority of studies on WWS reuse have been performed with aluminium-rich WWS (e.g. Babatunde and Zhao 2010;Ippolito et al 2003;Makris et al 2004;Yang et al 2009;Zhao et al 2007) and very few were based on ironrich WWS (e.g. Makris et al 2004;Leader et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One strategy was the use of the thickened alum sludge for co-conditioning and dewatering with the anaerobically digested sludge in MWWTP. The other strategy involves the use of dewatered alum sludge cakes in a fixed bed for P immobilization in reject water (Yang et al, 2009). However, from a holistic point of view, the process for reducing nutrient feedback and accumulation in MWWTP should duly consider N, P and OM removal, rather than P itself from the recycled reject water.…”
Section: Introductionmentioning
confidence: 99%
“…WTS can act as skeleton builder in the mixed sludge which makes the mixed sludge more incompressible and enhance the dewaterability (Lai and Liu, 2004). Also the phosphate concentration in the supernatant of the mixed sludge will decrease due to adsorption by WTS (Yang et al, 2009). The combined sludge can be dried in sludge drying beds and can be used for land application (Fig.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…High affinity of amorphous Al and Fe present in WTS for phosphorus along with large surface area of WTS makes WTS a potential adsorbent for phosphorus (Oliver et al, 2011;Wang and Pei, 2013;Yang et al, 2006). WTS has been used as adsorbent for phosphorus removal from sewage (Babatunde et al, 2008), agricultural wastewater , storm water runoff (O'Neill and Davis, 2012), aquaculture processing water (Mortula and Gagnon, 2007) and supernatant of the sludge thickening process and anaerobically digested sludge (Yang et al, 2009). No studies have been reported in the literature on the use of water treatment sludge as a coagulant for phosphate removal from the effluent of UASB reactor treating municipal wastewater.…”
Section: Introductionmentioning
confidence: 99%